Cell-mediated immunity in guinea pigs to subunits derived from hepatitis B surface antigen. - Cabral, G A (1975)
Guinea pigs immunized wit- hepatitis B surface antigen (HBSAg), types adw and ayw, and with two polypeptides (400,000 and 24,000 molecular weight) developed cell-mediated immunity (CMI), as determined by radioimmunoassay. Peritoneal exudate (PE) cells from guinea pigs immunized with the 40,000-molecular-weight polypeptide migrated poorly (30 to 88% inhibition) after challenge with the immunizing subunit or with purified HBSAg, type gdw or ayw. Response of the same PE cells to the 24,000-molecular-weight subunit was significantly reduced. Similar but less striking evidence for CMI was observed was PE cells derived from guinea pigs inoculated with purified type-specific HBSAg or with the 24,000-molecular-weight polypeptide. Humoral responses were predictable and showed a reasonable degree of correlation with the CMI response. PE cells from control animals inoculated with normal human serum or polyacrylamide gel were not inhibited after challenge with purified preparations of HBSAg or with the 400,000-molecular-weight polypeptide, but did show CMI with their respective immunogens. In addition, PE cells from guinea pigs inoculated with normal human serum were inhibited from migrating after challenge with the 24,000-molecular-weight subunit, suggesting that the latter may contain an antigenic determinant related to a human serum protein.